Penerapan Zahir Accounting Versi 5.1 Untuk Pengolahan Data Akuntansi Pada SMK Tridaya Jakarta - Saryoko, Andi; Janah, Miftahul; Sukmana, Sulaeman Hadi; Hidayat, Rahmat (www.bsi.ac.id, 2018)
The development of information technology can not be separated with a device called a computer. At this time the computer is needed in a company because by utilizing computer technology can make data processing more quickly and accurately and save storage space in archiving. SMK Tridaya accounting data processing is still manually so that there will be mistakes in recording transactions and takes a long time in working on financial statements. Therefore SMK Tridaya Jakarta requires a computer application program and to solve the problem the author using Zahir Accounting Software Version 5.1 as an alternative problem solvers in accounting data processing. Because by using zahir accounting data processing will be done automatically and can reduce errors that will occur in the data processing. And make effective and efficient in carrying out activities, especially in accounting data processing.